Degradation of ß-casomorphins and identification of degradation products during yoghurt processing using liquid chromatography coupled with high resolution mass spectrometry - Nguyen, D.; Busetti, F.; Johnson, Stuart; Solah, Vicky (Elsevier, 2018)
© 2017 Elsevier Ltd Liquid chromatography-high resolution mass spectrometry (LC-HRMS) was used to investigate the degradation of ß-casomorphin 5 (ß-CM5) and ß-casomorphin 7 (ß-CM7) by Streptococcus thermophilus and/or Lactobacillus delbrueckii ssp. bulgaricus, and to identify the degradation products forming during yoghurt processing. Bovine UHT milk was fermented with: (i) a single strain of L. delbrueckii ssp. bulgaricus, (ii) a single strain of S. thermophilus and (iii) the mixture of S. thermophilus and L. delbrueckii ssp. bulgaricus to pH 4.5 and then stored at 4 °C for 1 and 7 days. Results showed that L. delbrueckii ssp. bulgaricus and/or S. thermophilus completely degraded ß-CM5 and ß-CM7 upon fermentation to pH 4.5 and degradation products were significantly influenced by bacteria strains and storage time. Four peptides, ß-CNf60–61 (YP), ß-CNf62–63 (FP), ß-CNf64–66 (GPI) and ß-CNf62–66 (FPGPI) were tentatively identified through high resolution MS/MS experiments; however, it was not possible to confirm if either milk protein or ß-casomorphins was a source releasing these peptides. Nonetheless, in this study peptides YP and GPI were released by L. delbrueckii ssp. bulgaricus. This is the first time GPI has been identified and thus future investigation of its bioactivity is warranted.